2017
DOI: 10.3390/robotics6030018
|View full text |Cite
|
Sign up to set email alerts
|

Application of Augmented Reality and Robotic Technology in Broadcasting: A Survey

Abstract: Abstract:As an innovation technique, Augmented Reality (AR) has been gradually deployed in the broadcast, videography and cinematography industries. Virtual graphics generated by AR are dynamic and overlap on the surface of the environment so that the original appearance can be greatly enhanced in comparison with traditional broadcasting. In addition, AR enables broadcasters to interact with augmented virtual 3D models on a broadcasting scene in order to enhance the performance of broadcasting. Recently, advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 56 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Another factor that drops performance in dynamically changing environments is occlusion of markers which was noted in our previous work [10]. On this account, marker-less approaches have became a major focus [17]. This includes model-based approaches which use foreknown 3D models to localize objects and generate the pose estimation for the AR device.…”
Section: A Ar Calibration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor that drops performance in dynamically changing environments is occlusion of markers which was noted in our previous work [10]. On this account, marker-less approaches have became a major focus [17]. This includes model-based approaches which use foreknown 3D models to localize objects and generate the pose estimation for the AR device.…”
Section: A Ar Calibration Methodsmentioning
confidence: 99%
“…With the recent advances in machine learning algorithms, especially deep learning, and the higher computational capabilities of computers, networks can be trained to recognize 3D objects. An overview of current research is provided by Yan et al [17]. Recent publications by [19], [20] have focused on learning directly from 3D data.…”
Section: A Ar Calibration Methodsmentioning
confidence: 99%
“…Technologies, such as cameras, infrared sensors, hybrid sensors, and 2D and 3D markers, can all be implemented to identify a pattern and track its position in the real world. Robotic cameraman systems have been proposed to increase the quality of broadcasting systems and replace human operators [40]. It has been shown that robotic cameramen facilitate more precise and advanced interaction with virtual elements, and through zooming and multiple angle views, improve the performance of AR broadcasting in all sorts of environments.…”
Section: Ar In Entertainmentmentioning
confidence: 99%
“…Barcode has also been used in combination with AR for commercial purposes [17]. AR had also been used for broadcasting enhancement as mentioned by Yan and Hu [18] which in general depends on AR display, AR tracking, and robotic AR broadcast.…”
Section: State Of the Artmentioning
confidence: 99%